DAMPAK PERANG DUNIA II TERHADAP BUDAYA MASYARAKAT BIAK TIMUR (Impacts of World War II in East Biak Society) - Sonya M. Kawer (BALAI ARKEOLOGI PAPUA, 2019)
World War II was very influential to the eastern region of Indonesia and had left many remains in the areas that became the center or the liaison area of its power. Biak Numfor is one of the important areas in the historical process. There are many relics in the form of former hiding places of caves, houses, attributes of war, money, dizziness, places to eat and medical devices. The problem is how is the form and function and influence on the local community? Qualitative research with interview, observation, and literature study techniques, tried to formulate a strategy of World War II heritage tracks. The hope, this research can be used as an educational material for the history of Papua during the colonial period. Besides being a historical site that needs to be preserved and preserved and or developed as a cultural tourism object. ABSTRAK Perang Dunia II sangat berpengaruh ke wilayah timur Indonesia dan telahmeninggalkan bany a k tinggalan di daerah-daerah yang menjadi pusatatau daerah penghubung kekuasaannya. Biak Numfor menjadi salah satudaerah penting dalam proses sejarah. Disana banyak peninggalan berupabekas tempat pesembunyian gua-gua,rumah, atribut perang, uang, pening,tempat makan dan alat-alat kesehatan. Permasalahnya, bagaimana bentukdan fungsi serta pengaruh pada masyarakat setempat? Penelitian kualitatifdengan teknik waw a ncara, observasi, dan studi pustaka, berusahamerumuskan strategi jejak peninggalan Perang Dunia II terhadap budayamasyarakat setempat. Harapannya, penelitian ini dapat digunakan sebagaibahan pendidikan sejarah Papua di masa penjajahan. Selain juga sebagaisitus bersejarah yang perlu dijaga dan dilestarikan dan atau dikembangkansebagai objek wisata budaya.